The impact of stock market, exchange rate and oil price towards economic growth: cases of Malaysia / Dercy Piansin - Piansin, Dercy (2017)
This paper aim is to find out the positive and negative relationship between the stock market, oil price and exchange rate towards economic growth in Malaysia. In this study, we considered the economic indicator as the additional determinants. By the term of financial indicator, stock market is taken as a representative to the financial aspect. Meanwhile, for the economic indicator includes exchange rate (dollar to RM) and oil price, which is per barrel of price in USD. Hence, the monthly time series includes: stock price, exchange rate and oil price from the year 2005 to 2015 were modelled into a multiple regression model. The result of this study is the stock price and oil price have a positive relationship with the economic growth.